Monetary policy surprises and fiscal sustainability: the case of the Euro Area - Serena Ionta; António Afonso; José Alves (Economic Change and Restructuring, 2025)
We study the interaction between monetary and fiscal policies in the Euro Area, in particular the effect of monetary surprise shocks on real output and the price level under different fiscal sustainability regimes. We first estimate a time-varying Bohn (Q J Econ 113:949–963, 1998) rule using the Schlicht (2003) method. Then, we use a nonlinear local projection model for the Euro Area (aggregate data), Germany, Italy, and Portugal conditional on the fiscal regimes obtained in the first step. We find that the effect of monetary shocks depends on the degree of fiscal sustainability of each country. In the case of a more Ricardian regime, output and prices respond to monetary tightening by contracting. Instead, in the less Ricardian regime, the response is insignificant or even positive. Our results show that fiscal solvency is important for the effectiveness of monetary policy. The results are robust to different specifications and models.
Keywords: C32; E58; E62; E63; 330; Monetary surprises; Fiscal sustainability; Local projection models; Fiscal-monetary policy mix; Euro Area; Germany; Italy; Portugal